Discovery of Atmospheric‐Wind‐Driven Electric Currents in Saturn's Magnetosphere in the Gap Between Saturn and its Rings. Issue 19 (3rd October 2018) - Khurana, K. K.; Dougherty, M. K.; Provan, G.; Hunt, G. J.; Kivelson, M. G.; Cowley, S. W. H.; Southwood, D. J.; Russell, C. T.
Abstract: Magnetic field observations obtained by the Cassini spacecraft as it traversed regions inside of Saturn's D ring packed a genuine surprise. The azimuthal component of the magnetic field recorded a consistent positive perturbation with a strength of 15–25 nT near closest approach. The closest approaches were near the equatorial plane of Saturn and were distributed narrowly around local noon and brought the spacecraft to within 2, 550 km of Saturn's cloud tops. Modeling of this perturbation shows that it is not of internal origin but is produced by external currents that couple the low‐latitude northern ionosphere to the low‐latitude southern ionosphere. The azimuthal perturbations diminish at higher latitudes on field lines that connect to Saturn's icy rings. The sense of the current system suggests that the southern feet of the field lines in the ionosphere leads their northern counterparts. We show that the observed field perturbations are consistent with a field‐aligned current whose strength is ~1 MA/radian, that is, comparable in strength to the planetary‐period‐oscillation‐related current systems observed in the auroral zone. We show that the Lorentz force in the ionosphere extracts momentum from the faster moving low‐latitude zonal belt and delivers it to the northern ionosphere. We further show that the electric current is generated when the two ends of a field line are embedded in zonal flows with differing wind speeds in the low‐latitude thermosphere. The wind‐generated currents dissipate 2 × 10 11 W of thermal power, similar to the input from the solar extreme ultraviolet flux in this region. Plain Language Summary: The Cassini spacecraft observed strong electric currents aligned along Saturn's magnetic field as it traversed regions inside Saturn's D ring. Modeling and analysis of these currents show that their origin lies in the neutral winds observed in the upper atmosphere of Saturn. The wind‐generated currents dissipate a modest amount of energy, which is roughly equal to that coming from solar extreme ultraviolet rays. Key Points: During Cassini's Grand Finale orbits, the spacecraft identified strong but variable field‐aligned currents inside Saturn's D ring The current is generated when the two ends of a field line are embedded in zonal atmospheric flows that have differing wind speeds The wind‐generated currents dissipate 2 × 10 11 TW of thermal power in the low‐latitude thermosphere, similar to the input from the solar EUV flux in this region